基于时序AR与灰色GM模型的滚动轴承故障诊断研究 - 陈瑞华; 杨宗伟 (Jixie chuandong)
Aiming at the problems of roller bearing fault diagnosis,gray theory and auto-regressive combination forecasting model is put forward,and the combination model has been build. The methodology developed decomposes the signal in intrinsic oscillation modes first,to translate the non-stationary signals into stationary signals. Then the autoregressive （AR） model of the selected IMF is established. The rough trend of the wear particle content change can be reflected through gray theory,and the detail of the change can be reflected through auto-regressive model. By testing and comparing a set of graphic data,the result shows that the combination model has a better forecasting result.